PENGARUH PEMAHAMAN PERPAJAKAN, KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN, DAN RISIKO TERDETEKSI FISKUS TERHADAP KEPATUHAN WAJIB PAJAK UMKM (STUDI PADA WAJIB PAJAK UMKM DI KOTA BANDA ACEH) - Riska Faradhila; Wida Fadhlia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine the effect of the tax understanding, taxpayer awareness, service quality and the risk of tax authorities detected towards taxpayer compliance of MSMEs. The taxpayer of micro, small, and medium enterprises (MSMEs) in Banda Aceh are the respondent. Data collected trough questionnaires. Data analized using the method of multiple linear regression, partial test (t test), and simultaneously test (together), while processing the data using SPSS 23. The result of this study shows that (1) the tax understanding, taxpayer awareness, service quality, and the risk of the tax authorities influence on taxpayer compliance of MSMEs simultaneously, (2) the tax understanding detection effect on taxpayer compliance of MSMEs, (3) the taxpayer awareness detection effect on taxpayer compliance of MSMEs, (4) the quality service detection effect on taxpayer compliance of MSMEs, (5) the risk of tax authorities detected effect on taxpayer compliance of MSMEs”.